SISTEM PEMESANAN PEMINJAMAN BUKU PERPUSTAKAAN BERDASARKAN KATALOG BERBASIS WEB (Information Technology and Telematics, 2015)
Educational institutions such as Madrasah Aliyah Purwodadi which organizes educational services have sub sections that support in improving the quality of education the sub-section is library. During this time the library members in the process of borrowing and repayment are still using manual way making it less efficient and because of the insufficient number of books sometimes members who want to borrow running out of books will be borrowed. Media that has not been exploited by Madrasah Aliyah Purwodadi is the use of a PC (Personal Computer) to make the process of borrowing books online. Development “Ordering System Borrowed Library Boook Based On Catalog And Web Based” purpose to improve service and facilitate members in the process of borrowing books without fear of running out of books to be borrowed   Kata Kunci : Library information system,ordering, book, catalog